Design of a Spray Tower for the Granulation of Melt - Abd Ali, Kaiser Muslem (Nahrain University College of Engineering Journal, 2015)
In this paper a simulation of cooling-solidification tower was presented, sprayed droplets is one of major methods for prilling of melt. Traditionally, this is carried out in an empty tower, and the equipment requirements for producing larger particles is very high, for analysis and simulation, mathematical model of tower, the effect of molten drop size on height of tower, heat and mass transfer coefficients are estimated according to empirical correlations. Estimations are considered based on concept of energy and mass transfer correlation equations. The results showed that the height of equipment is greatly affected by atomized particle size.